Alocação de água no Ceará: diagnóstico e desafios - Araújo, Bruno Aragão Martins de (2012)
In semiarid regions, such as the State of Ceará, and arid is a difficult scenario of water scarcity due to various factors like irregular rainfall, high temperatures and consequently high rates of evaporation, etc.. With a high demand and an offer not so abundant, it is necessary to water management that enables all stakeholders in this feature can be seen in their different needs and quantities. Water allocation is a process of division of property between individuals with often conflicting interests. The objective of this study is to analyze the decision-making process of water allocation Basins of the State of Ceará, identifying their similarities and differences in methodology. For this, interviews were conducted, as well as questionnaires during meetings negotiated allocation. What is observed is that some basins have similar rituals and procedures, while in others there are isolated actions. Armed with this information were identified and proposed improvements to the system of negotiated allocation processes in decision-making meetings allocation negotiated basins.